Datasets for "Optimising Complexity and Learning for Photonic Reservoir Computing with Gain-Controlled Multimode Fibres" - Giulia Marcucci (21709711) (2025)
The data is associated with the main text and supplementary figures. The dataset is provided in .fig format and separated into folders. They can be opened by open-source software such as Octave. Giulia Marcucci, Luana Olivieri, and Juan Sebastian Totero Gongora, "Optimising complexity and learning for photonic reservoir computing with gain-controlled multimode fibres", Front. Nanotechnol. 7:1631564 (2025). DOI: 10.3389/fnano.2025.1631564